2001
DOI: 10.1136/gut.49.3.395
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a motilin receptor agonist (ABT-229) on upper gastrointestinal symptoms in type 1 diabetes mellitus: a randomised, double blind, placebo controlled trial

Abstract: Introduction-Erythromycin, a motilin agonist, is a potent prokinetic. ABT-229 is a specific motilin agonist that dose dependently accelerates gastric emptying. Dyspepsia and gastroparesis are common problems in type 1 diabetes mellitus. We aimed to evaluate the eYcacy of ABT-229 in symptomatic diabetic patients with and without delayed gastric emptying. Methods-Patients with type 1 diabetes and postprandial symptoms were randomised (n=270). Based on a validated C 13 octanoic acid breath test, patients were ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
124
0
6

Year Published

2002
2002
2015
2015

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 155 publications
(132 citation statements)
references
References 39 publications
2
124
0
6
Order By: Relevance
“…After 4 weeks, ABT-229 in a dose of 10 mg b.d., exacerbated symptoms when compared with placebo and this was the case irrespective of whether patients had delayed gastric emptying or not. 20 Mechanisms that may be relevant to the generation of symptoms in patients with diabetes include slow gastric emptying, changes in antral or fundic tone, and visceral hypersensitivity which may all be influenced by hyperglycaemia. 1, 2 It has been suggested that the effect of motilin agonists on upper gastrointestinal symptoms may relate to an adverse effect on postprandial fundic relaxation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…After 4 weeks, ABT-229 in a dose of 10 mg b.d., exacerbated symptoms when compared with placebo and this was the case irrespective of whether patients had delayed gastric emptying or not. 20 Mechanisms that may be relevant to the generation of symptoms in patients with diabetes include slow gastric emptying, changes in antral or fundic tone, and visceral hypersensitivity which may all be influenced by hyperglycaemia. 1, 2 It has been suggested that the effect of motilin agonists on upper gastrointestinal symptoms may relate to an adverse effect on postprandial fundic relaxation.…”
Section: Discussionmentioning
confidence: 99%
“…[2][3][4] In view of the potency of intravenous erythromycin in accelerating gastric emptying when administered acutely in diabetic gastroparesis, motilides that lack antibiotic activity have been developed. 4,20 Both animal and human studies have established that KC 11458 accelerates gastric emptying. [22][23][24][25][26] In healthy volunteers, single oral doses of KC 11458 ranging from 4 to 32 mg accelerated gastric emptying of solids as assessed by a breath test.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result, more potent motorstimulating EM derivatives were developed without antibiotic activity: the motilides (Omura et al, 1987). Recently the clinical development of the most promising motilide ABT-229 was stopped because of its failure to improve symptoms in patients with functional dyspepsia with normal or delayed gastric emptying (Talley et al, 2000) and in patients with type 1 diabetes mellitus (Talley et al, 2001). The authors of the studies with ABT-229 concluded that there was no future for drugs with the prokinetic profile of the motilides, but others have argued that ABT-229 had undesirable properties that may be avoided in new motilides (Tack and Peeters, 2001;Camilleri, 2002).…”
mentioning
confidence: 99%
“…In order to overcome this issue, a number of motilin derivatives that have no antibiotic property have been developed. Unfortunately, the prokinetic effects of these new agents are less durable, and are most likely due to the rapid development of drug tachyphylaxis [74][75][76] .…”
Section: Issues Related To the Development Of Bacterial Resistancementioning
confidence: 99%